Corporate social responsibility in a unionised duopoly - Fanti, Luciano; Buccella, Domenico (Estudios de Economía, 2019)
It is commonly believed that the choice of adopting Corporate Social Responsibility (CSR) behaviours is beyond the scope of profit enhancement. In a unionised oligopoly with centralised wage setting and decreasing returns to scale technology, the present paper shows that the owners’ choice of the CSR engagement level is dictated by the firms’ purely selfish profit-seeking objective. In fact, profits under CSR are higher than under the standard profit-maximising rule. Moreover, the union, consumers and the social welfare on the whole with CSR are higher than without CSR: the firms’ owners social concern leads to a Pareto-superior outcome.